The Use of an Incentive Program to Increase Motivation for Academic Performance - Hickmann, Sara A.; Bartolomew, Nate; McKenzie, Thomas (My University, 1997)
The effects of an incentive program (Free Hours Points Program) on academic performance were examined. Sixty student-athletes on academic probation (less than a 2.25 GPA) at a Division I university participated. Points were awarded for positive, measurable efforts towards improving academic standing. Although grade point average (GPA) did not significantly increase from one year to the next, 62% of student-athletes did demonstrate improvement on this measure. Total points earned by each individual was not significantly correlated to GPA, however, class year was significantly negatively correlated with points earned, suggesting that this type of intervention may be more effective with younger student-athletes.
Keywords: academic performance; models; at-risk